From Performance Sports to Sports for All: Romania 1945-1965. Legal Aspects - PUNI, Rares (Mediterranean Journal of Social Sciences, 2012)
The establishment of the communist regime in Romania in 1945 marked the beginning of a series of profoundtransformations in the Romanian political and social life. These changes also affected the field of sports activities, which were, atthe time, at the initial point of their institutional organization.Our research aims at analyzing, in a critical manner, the mainlegislative regulations regarding sports life implemented between 1945-1965. Their main goal was to promote the benefits ofpracticing physical activities regularly, not only by performance sportsmen, but also by the majority of the population. Thisinitiative matched the international tendency commonly called â€œsports for allâ€, advertised by the founding-father of modernOlympic games â€“ Pierre de Coubertin. The laws issued by the communist authorities stipulated the establishment of nationalinstitutions and organizations in charge with the situation of the Romanian sports field, with the financial aspects requested bysuch endeavor and with the funding provided by the government. Unfortunately, many of the objectives formulated in these lawswere left only in their initial form or were completed much later that initially intended.